Penerapan Model Project Based Learning untuk Meningkatkan Kreativitas Siswa dalam LKPD Mata Pelajaran Al-Qur’an Hadist Kelas 3 MI Mambaul Ulum Kaliacar - Juherni Juherni; Khalipah Khalipah (STIKes Ibnu Sina Ajibarang, 2025)
The aim of this study was to improve students' creativity in completing Student Worksheets (LKPD) through the implementation of the Project Based Learning (PjBL) model for third-grade students at Madrasah Ibtidaiyah Mambaul Ulum Kaliacar. The research method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles. Each cycle included the stages of planning, action, observation, and reflection. Data collection techniques involved observation, interviews, questionnaires, and documentation, while data analysis was conducted using descriptive qualitative and quantitative methods. The results of the study showed that the implementation of PjBL significantly improved students' creativity in completing LKPD in the Al-Qur'an Hadist subject. This was evident from the increase in the average creativity score of students from 65% in the first cycle to 85% in the second cycle. In addition, the level of student engagement in the learning process rose from 70% to 85%, and student satisfaction with the implementation of PjBL reached 80%. The obstacles encountered in this study included limited time and differences in students' initial abilities, but these challenges could be overcome with intensive guidance from the teacher. Thus, the implementation of Project Based Learning (PjBL) proved effective in enhancing students' creativity and learning motivation. It is recommended that teachers further optimize their roles as facilitators and consider students' characteristics to achieve more optimal results.